The Influence of Liquid Load Motion on Rollover Stability of Road Tankers - Tesar, Miroslav (Communications - Scientific letters of the University of Zilina, 2005)
Rollover threshold is an essential factor in research into road tanker behavior since the accidents involving these vehicles frequently have fatal consequences, especially when their load is of a flammable or toxic nature. The following article presents a method of identifying the influence of liquid motion in a partially filled road tanker. The method is based on simulation using a mathematical model developed with the help of MSA (Multi-body System Analysis) software. This software enables the user to evaluate all the factors that influence rollover stability. Mechanical pendulum methodology has been used to simulate the liquid motion. The road tanker model was tested in compliance with the results obtained by measuring carried out on a SCANIA 124 L truck combined with a ZVVZ trailer. Simulation tests were carried out for the drive on a circular track and in a drive around a roundabout, which is considered the most dangerous manoeuvre in respect to vehicle rollover.